After Trilce, what? Vallejo’s creation in the period 1923-1929 - Arredondo Palacios, Martín (2022)
This article provides an overview of the work produced by Vallejo in the first part of his stay in Paris. It seeks to show how, although there are natural continuities between what he produced in Peru and what he wrote in Europe, the period 1923-1929 represents a process of decantations and discoveries of great significance for the poet’s later work (written in the context of his adherence to Marxism and in a particularly tense political context). In the years of my interest, Vallejo writes from the aesthetics of the vital (which supposes an ethic) and from his position-taking in the three imbricated literary fields in which he participates: the French, the Peruvian and the Spanish American writer in Paris.